2018
DOI: 10.22587/ajbas.2018.12.9.11
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Mobile Marketing among Young Malaysian Customers

Abstract: Despite the tremendous penetration rate of mobile phones worldwide, mobile users still show negative attitudes toward mobile marketing communications (Watson, McCarthy, & Rowley, 2013). In Malaysia, mobile marketing is relatively at its early stages (Lee & Wong, 2016). According to MCMC's survey (2017) only 48.8% of participants used online shopping in Malaysia. Moreover, based on Rakuten (2010) study, 71% of Malaysian online shoppers tend to regret their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Taking the results it was found that consumer attitude towards mobile marketing influences their intention to purchase a product or service. This finding is consistent with studies done by other researchers (Bauer et al 2005;Laksamana, 2016;Saeed & Bekhet, 2018;Alameer et al 2022;Ismail et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taking the results it was found that consumer attitude towards mobile marketing influences their intention to purchase a product or service. This finding is consistent with studies done by other researchers (Bauer et al 2005;Laksamana, 2016;Saeed & Bekhet, 2018;Alameer et al 2022;Ismail et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Laksamana (2016) found a positive correlation between attitude and purchase intention in the banking sector. In a study of young Malaysian consumers, Saeed and Bekhet (2018) also confirmed a relationship between attitude towards mobile marketing and intention to use mobile marketing services. Ismail et al (2022) research corroborated that a positive attitude toward mobile marketing has an impact on the intention to use mobile marketing services.…”
Section: Technology Acceptancementioning
confidence: 69%
“…The adoption of mobile marketing by SMEs is determined by multiple factors such as cost, alignment with the business model, efficacy, and target customers (Saeed & Bekhet, 2018). For example, young customers appear to be willing to engage with mobile marketing messages when there is a positive perception of ease of use, usefulness, entertainment value and personal attachment (Saeed & Bekhet, 2018).…”
Section: Mobile Marketing and Customer Retentionmentioning
confidence: 99%
“…Based on the participants' responses, it is evident that awareness of mobile marketing is one of the prerequisites influencing mobile marketing adoption. This means customers will be willing to engage with mobile marketing when they perceive its easy use, entertainment, and personal value (Saeed & Bekhet, 2018). Because SMEs can organise their knowledge into a coherent whole, this allows them to learn new concepts by connecting them to what they already know.…”
Section: Knowledge Of the Conceptmentioning
confidence: 99%